MU-SR STUDIES OF SPIN EXCITATIONS IN POLYANILINE - Pratt, F; Valladares, R; Pattenden, P; Blundell, S; Hayes, W; Monkman, A; Nagamine, K (1995)
Muon techniques have been used to study the spill excitations in polyaniline. The relaxation rate provides information about the spin dynamics. 1D spin diffusion is observed at low temperature in non-metallic materials with a crossover to 2 or 3D behaviour at higher temperature. In metallic polyaniline, in contrast to the undoped cases, the relaxation is rapidly quenched by field at all temperatures. Static and dynamic terms in the relaxation can be separated. The dynamic term shows a high field cutoff which occurs around 25 G at 20 K. This relaxation behaviour indicates a broad spectrum of spin fluctuations concentrated at frequencies in the region below 0.3 MHz. This is a frequency region that is somewhat lower than previously studied by other probes of spin dynamics.